Karakteristik Morfometrik Kambing Lokal di Kecamatan Tambang dan Kecamatan Siak Hulu Kabupaten Kampar - M Zaki; Putri Zulia Jati; Maulina Novita; Rahmat Hidayat (Journal of Engineering Science and Technology Management, 2021)
This study aims to determine the Morphometric Characteristics of Local Goats in Tambang District and Siak Hulu District, Kampar Regency. The method used in this study is the method of observation and interviews with breeders which were conducted to obtain information about local goats in Siak Hulu District and Tambang District, Kampar Regency. The sampling technique was purposive sampling, namely aged 12-36 months, female goats were not in a state of pregnancy, with a total sample of 60 heads consisting of 30 males and 30 females for each sub-district. The data collected are qualitative characteristics which include: color and pattern of coat color, ear shape and backline. Quantitative properties which include: Face Length, Ear Length, Bust, Chest Width, Inside Chest, Body Length, Shoulder Height, Hip Height, Hip Width, Front Leg Length, Length, Back Leg, Tail Length, and Body Weight. The data obtained in this study were analyzed descriptively and presented in the form of arithmetic mean, standard deviation, and coefficient of variation. Based on the results of morphometric observations of the body size of male and female Kacang goats in Tambang District and Kuok District, the average length of the face, ear length, chest circumference, chest width, chest length, body length, shoulder height, hip height, hip width, leg length was obtained. front, hind legs length, tail length, and body weight were not significantly different (P>0.05).